Urbanization Vs. Environmental Quali ty: Some Observation In Telipok, Sabah,Malaysia. - Ismail Abd Rahim; Sanudin Tahir; Baba Musta; Rodeano Roslee (2018)
The study area is underlined by Crocker Formation of Eocene to Early Miocene age and The study area is underlined by Crocker Formation of Eocene to Early Miocene age and Quaternary deposit. Rapid urbanization activities have caused changes in land use. These activities accelerate higher rate of weathering, surface runoff, soil erosion and siltation. Urbanization processes may contribute to exposure of impervious surface, loss of vegetation cover, modification of slope gradient and drainage system. This study provides strong evidence that urbanization at the study area negatively affects the natural environment. Soil erosion, siltation, poor water quality and flash floods are common within the study area in the event of heavy rainstorm. The main factors causing environmental problem in the study area are natural (geology, meteorology, geography, topography and drainage system) and human (lack of proper planning, human activities and community’s attitude). Therefore, any activity which potentially causing environmental problem must be implemented efficiently. Strict enforcement of environmental (soil erosion, siltation, water quality and flash flood) regulation and sustainable land use planning and management is crucial. Serious efforts to increase the community’s awareness to environmental problem and reconstruction of natural ecosystem must be taken. This is to ensure that future activities in the study area will not cause further damage to natural environmental condition or ecosystem.